A systematic review and meta-analysis of primary teeth caries studies in Gulf Cooperation Council States - W. Al Ayyan; M. Al Halabi; I. Hussein; AH. Khamis; M. Kowash (Elsevier, 2018)
Objectives: The aim of the study was to evaluate the prevalence and severity of dental caries in pre-school children in the Gulf Cooperation Council (GCC) area. Methods: A search of literature was conducted to identify articles of dental caries in primary dentitions published during the period from January 1st, 1992 to June 30th, 2016. PubMed, Google Scholar search, and hand searching of journals was conducted to identify relevant articles. The search strategy employed both dental subject headings and free-text terms. Results: Out of a total of 193 studies that fit the initial inclusion criteria, 159 studies were further excluded. Only 34 studies were included in the systematic review and meta-analyses. The overall mean dmft in the primary teeth was 5.14 with prevalence of 80.9% in the GCC area. A high level of heterogeneity in the selected studies was found as demonstrated by Q-value of 2538.501 (df = 21) and I2 value of 99.17%. However, the funnel plots showed symmetrical shape at the bottom in both dmft and prevalence studies indicating absence of publication bias, which was also confirmed by insignificant result of Egger's regression statistical test (Egger's test P = 0.179-0.358). Conclusion: Caries in the primary dentition in the GCC States was high both in terms of mean dmft (5.14) and prevalence (80.95%). Keywords: Dental caries, Children, Primary teeth, Prevalence, Dmft, GCC countries